Leadership Styles and its effect on Performance of Commission Nationale Indépendante des droits de l’ Homme (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study set out to analyse the influence of leadership styles on organizational performance with reference to the Commission Nationale Indépendante des Droits de l’Homme. The study employed correlational research design and opted a quantitative approach. Survey questionnaire was used to collect data from the accessible population of 41. The results indicate that there is a positive and significant relationship between Transformational leadership and organizational performance (r=.589, p-value